2018
DOI: 10.1039/c8cp02282h
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectrum and intermolecular potential energy surface of the CO–O2 dimer

Abstract: Only a few weakly-bound complexes containing the O2 molecule have been characterized by high resolution spectroscopy, no doubt due to the complications added by the oxygen molecule's unpaired electron spin. Here we report an extensive infrared spectrum of CO-O2, observed in the CO fundamental band region using a tunable quantum cascade laser to probe a pulsed supersonic jet expansion. The rotational energy level pattern derived from the spectrum consists of stacks of levels characterized by the total angular m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 64 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…It has been demonstrated that such calculations are accurate for other Van der Waals dimers. [11][12][13][14] Probability Density (PD) and wavefunction cut plots are used to label the energy levels. We find significant coupling between in-plane and out-of-plane coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that such calculations are accurate for other Van der Waals dimers. [11][12][13][14] Probability Density (PD) and wavefunction cut plots are used to label the energy levels. We find significant coupling between in-plane and out-of-plane coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Using the CCSD(T)-F12b 1 approach (Adler et al 2007), along with the VTZ-F12 2 basis set (Hill et al 2010), we derived 4D PESs for the HC 2 NC-H 2 and HNC 3 -H 2 van der Waals (vdW) systems within the rigid rotor approximation. As we have done in the past for other vdW linear dimers (Wang et al 2016;Donoghue et al 2016;Barclay et al 2018;Desrousseaux et al 2019;Castro-Juárez et al 2019;Quintas-Sánchez et al 2020), the 4D PES analytical representation was constructed using an automated interpolating moving least squares methodology (Dawes et al 2010;Majumder et al 2016), implemented in the recently released software-package AUTOSURF (Quintas-Sánchez & Dawes 2019). The global estimated root-mean-squared fitting error tolerance was 0.33 cm −1 for both PESs, and the total number of symmetry unique points needed to reach that target was 6095 for HC 2 NC-H 2 and 4172 for HNC 3 -H 2 .…”
Section: Hc 2 Nc-h 2 and Hnc 3 -H 2 Potential Energy Surfacesmentioning
confidence: 99%
“…As we have done in the past for other vdW linear dimers, [1][2][3][4][5][6][7][8]24,25 the 4D PES analytical representation was constructed using an automated interpolating moving least-squares methodology, which has been recently released as a software package under the name AUTO-SURF. 12 As usual, 26 a local fit was expanded about each data point, and the final potential is obtained as the normalized weighted sum of the local fits.…”
Section: Analytical Representationmentioning
confidence: 99%
“…Email: tucker.tarrington@queensu.ca, xgwang.dalian@gmail.com tonian for the nuclei. Examples include (OCS) 2 , 1 (CO) 2 , 2 (CO 2 ) 2 , 3 CO 2 -CO, 4 CO 2 -CS 2 , 5 (NNO) 2 , 6 CO 2 -HCCH, 7 O 2 -CO, 8 O 3 -Ar, 9 CO-N 2 , 10 CS-Ar and SiS-Ar. 11 In each case, guided by our automated fitting algorithm, electronic energies were computed using coupled-cluster theoryusually either CCSD(T) or the explicitly-correlated variant CCSD(T)-F12b-combined with large basis sets, often extrapolated towards the complete basis set (CBS) limit.…”
Section: Introductionmentioning
confidence: 99%